2013
DOI: 10.1128/jvi.00554-12
|View full text |Cite
|
Sign up to set email alerts
|

CHD6, a Cellular Repressor of Influenza Virus Replication, Is Degraded in Human Alveolar Epithelial Cells and Mice Lungs during Infection

Abstract: The influenza virus polymerase associates to an important number of transcription-related proteins, including the largest subunit of the RNA polymerase II complex (RNAP II). Despite this association, degradation of the RNAP II takes place in the infected cells once viral transcription is completed. We have previously shown that the chromatin remodeler CHD6 protein interacts with the influenza virus polymerase complex, represses viral replication, and relocalizes to inactive chromatin during influenza virus inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 92 publications
1
14
0
Order By: Relevance
“…We recently characterized the involvement pf the PB2 and PA subunits in RNAP II degradation, as well as the contribution of specific subunit residues to this process, which correlates with pathogenicity in mice (27). We also showed that the CHD6 chromatin remodeler is specifically degraded after influenza virus infection in cultured cells and in a mouse model (28).…”
mentioning
confidence: 96%
“…We recently characterized the involvement pf the PB2 and PA subunits in RNAP II degradation, as well as the contribution of specific subunit residues to this process, which correlates with pathogenicity in mice (27). We also showed that the CHD6 chromatin remodeler is specifically degraded after influenza virus infection in cultured cells and in a mouse model (28).…”
mentioning
confidence: 96%
“…Additionally, CHD6 is a DNA dependent ATPase. CHD6 protein is expected to function as a transcriptional repressor and it has been shown to be interact with RNA Pol II proteins (Lutz et al, 2006) and to be involved in the cellular repression of viral replication (Fertey et al, 2010;Alfonso et al, 2011;Alfonso et al, 2013 …”
Section: Descriptionmentioning
confidence: 99%
“…It associates with viral ribonuclear proteins in infected cells (Alfonso et al, 2011). Loss of CHD6 by siRNA silencing results in an increased viral replication, while in lungs of infected mice, CHD6 is degraded upon infection and exposure to the three subunits of the viral polymerase (Alfonso et al, 2013). Recent reports also indicate that CHD6 interacts with human papillomavirus proteins, binding and repressing the expression of oncogenes (Fertey et al, 2010).…”
Section: Influenza/human Papillomavirusmentioning
confidence: 99%
“…The RNAP II and CHD6 degradation observed seems to be a general feature triggered by influenza A viruses (10,12), but we have previously reported that degradation of RNAP II does not occur upon infection with the attenuated A/PR/8/34 (PR8) strain (9), which would contribute to the attenuated phenotype of the strain. However, a hypervirulent PR8 (hvPR8) variant, which multiplies much faster than standard PR8 (lvPR8) in infected cells and is more virulent in mice than the parental PR8 virus, efficiently induces RNAP II degradation (9).…”
mentioning
confidence: 96%
“…More recently, a degradative process affecting RNA polymerase II (RNAP II) (9)(10)(11), as well as CHD6 chromatin remodeler (12), has been reported. Degradation and disabling of host cell factors involved in genome expression may contribute to hijacking the metabolism of the infected cell and to suppressing the establishment of the host antiviral defense against viral pathogens, contributing to viral pathogenicity.…”
mentioning
confidence: 99%